Sensitivity of charged particle activation analysis for long-lived radioactive nuclide determination. Issue 9 (3rd October 2019) - Oshima, Masumi; Yamaguchi, Yurie; Asai, Masato; Tsukada, Kazuaki; Goto, Jun; Bamba, Shigeru; Bi, Chunlei; Morimoto, Takao
ABSTRACT: Charged Particle Activation Analysis (CPAA) utilizing an 8-MeV proton beam has been studied for determination of 35 long-lived radioactive nuclides. We accumulated the reaction cross section and nuclear decay data by referring to nuclear database supplied by National Nuclear Data Center in Brookhaven National Laboratory. We also calculated the reaction cross sections by using statistical model code ALICE. By using the nuclear data, we have derived determination sensitivity of the radioactive nuclides relative to unit weight and specific radioactivity. The result indicates that several hardly measurable nuclides with long half-lives such as 135 Cs, 244 Pu, 129 I, 126 Sn, 93 Mo, 107 Pd, 236 U, 248 Cm, and 237 Np have high sensitivity. It may be concluded that CPAA can be applied to determination of several long-lived nuclei and will provide a quick and non-destructive analysis method.